Prevalence and risk factors of thoracic aortic dilatation detected incidentally in adjuvant radiotherapy planning CT scans in patients with breast cancer - Aada Lattu; Petteri Kauhanen; Ari Mennander; Marja Hedman; Mona Laaksonen; Irina Rinta-Kiikka; Tanja Skyttä; Otso Arponen (Scientific Reports)
Abstract Thoracic aortic dilatations (TADs) are commonly detected incidentally. A TAD may develop into aortic aneurysm and subsequently lead to aortic dissection, a highly lethal condition. Earlier detection of TADs could improve the surveillance and surgical management of aneurysms, potentially reducing aortic ruptures. The opportunistic use of thoracic sectional imaging studies performed for other indications, including breast radiation therapy planning, could be used to detect TADs. However, the frequency of TADs and the clinical risk factors for TADs in females undergoing adjuvant breast radiation therapy remain unknown. We retrospectively collected a consecutive cohort of 861 females with breast cancer who underwent adjuvant radiotherapy planning with computed tomography (CT). Using CT scans, we manually measured thoracic aortic dimensions on the hospital’s dedicated picture archiving and communication software (PACS). Following the European Society of Cardiology guidelines, a segment of the aorta was considered dilated when its maximal diameter exceeded 40 mm. Additionally, we collected clinical patient data regarding known risk factors predisposing patients to TADs. Out of 861 patients, 80 (9.3%) had a TAD. Compared to those without any TADs, patients with at least one TAD were older (71.3 ± 9.7 years vs. 62.9 ± 11.7 years; P < .001) and more frequently displayed hypertension (62 [77.5%] vs. 354 [45.3%], P < .001), a history of a TIA or stroke (10 [12.5%] vs. 36 [4.6%], P = .007), and aortic valve insufficiency (10 [12.5%] vs. 51 [6.5%], P = .047). The opportunistic use of radiotherapy planning CT scans allows earlier TAD diagnosis, and a significantly large number of female patients (9.3%) had at least one abnormal thoracic aortic dimension. This finding could indicate a need to consider a systematic screening of TADs in patients undergoing adjuvant radiotherapy.